Analisis Metode Pendidikan Abdullah Nashih Ulwan dalam Pendidikan Nilai Agama dan Moral Anak Usia Dini: Analisis Jurnal Sinta 2-5 - Adwiah, Amalia Rabiatul; Karomah, Rosi Tunas; Juleha, Siti (NANAEKE: Indonesian Journal of Early Childhood Education, 2024)
Abdullah Nasih Ulwan discussed a lot regarding the methods used in moral and religious education in early childhood which parents and educators apply. This research aims to determine Abdullah Nasih Ulwan’s educational methods regarding religious and moral values ​​education for early childhood. The method used in this research is qualitative research with a literature study approach. The data obtained in this research used documentation, namely searching for data in the form of articles in the journals Sinta 2 to Sinta 6, totaling 15 articles related to Abdullah Nashih Ulwan’s educational methods in religion and morals. The research instrument is the researcher’s key instrument. Content analysis is used as an analytical technique in research. The findings of this research are that there are 5 methods used in implementing moral religious education for children by Abdullah Nashih Ulwani, including the method of example, habituation, advice, attention and supervision, and the method of punishment. This method can be applied well in children’s moral education as a first step in preparing children to become useful people in future life.